EARLY AGE SUSTAINABILITY: TURNING KNOWLEDGE INTO ACTION THROUGH EDUCATIONAL AND INTERACTIVE ACTIVITIES (International Journal of Engineering Sciences & Management Research, 2018)
Fostering sustainability by supporting young people in the United Kingdom (UK) in activities and engagement with sustainable practices has significant long-term benefits. In order to promote sustainability in schools we designed a programme: “Sustainability: turning knowledge into action” that supported participation and disseminated the merits of sustainability to school children. We utilised open source materials to facilitate an introduction to the concepts of sustainability and its consequences. We used a participatory approach where students take ownership of activities as they form an understanding of how sustainable practices affect their lives and wider community. Preliminary results indicated that early training and support of young people increased involvement and provided a framework from which active participation developed into greater understanding of sustainability and the burgeoning necessity of living in a sustainable environment